Critical role of biomass burning aerosols in enhanced historical Indian Ocean warming - Yiqun Tian; Shineng Hu; Clara Deser (Nature Communications, 2023)
Abstract The tropical Indian Ocean (TIO) has experienced enhanced surface warming relative to the tropical mean during the past century, but the underlying mechanisms remain unclear. Here we use single-forcing, large-ensemble coupled model simulations to demonstrate that changes of biomass burning (BMB) aerosols have played a critical role in this TIO relative warming. Although the BMB aerosol changes have little effect on global mean temperatures due to regional cancellation, they significantly influence the pattern of warming over the tropical oceans. The reduction of BMB aerosols over the Indian subcontinent induces a TIO warming, while the increase of BMB aerosols over South America and Africa causes a cooling of the tropical Pacific and Atlantic, respectively. The resultant TIO relative warming leads to prominent global climate changes, including a westward expanded Indo-Pacific warm pool, a fresher TIO due to enhanced rainfall, and an intensified North Atlantic jet stream affecting European hydroclimate.